Melacak Tradisi Menulis Ulama Indonesia Abad Ke-19-21 (KH. Hasyim Asy’ari dan Ramli Abdul Wahid) - Rasyid Anwar Dalimuthe; Masruroh Lubis; Ruslan Efendi (STAI Serdang Lubuk Pakam, 2022)
The tradition of writing among scholars has deep roots in various Islamic disciplines. Many works of scholars produced from the writing tradition strongly encourage the development of science, and Islam itself is very concerned about the development of science. This study aims to analyze the writing traditions of Indonesian ulama in the 19-21 century, which in this case is focused on KH. Hasyim Asyari and Ramli Abdul Wahid. The research method used in this research is a qualitative method based on literature study. The results of the discussion. First, the tradition of writing is a very important activity in the progress of the ummah and the nation. So it is hoped that every generation has a high ability to make their best writings for the advancement of the next generation. Second, in writing a work, of course, there is a strong belief that fosters noble intentions. And writing also requires strong supporting factors such as socio-political, time and economic. The three prominent and productive scholars, including Kiai Hasyim Asy'ari, are still remembered and proud to this day. Likewise with Prof. Dr. H. Ramli Abdul Wahid, MA who is certainly a prominent scholar, especially in North Sumatra Province, with his works that have provided developments in the world of Islamic education, especially.